Imidazole and Benzimidazole Modified Half-Sandwich IridiumIIIN-Heterocyclic Carbene Complexes: Synthesis, Anticancer Application, and Organelle Targeting - Liu, Xicheng; Han, Yali; Ge, Xingxing; Liu, Zhe (Frontiers in Chemistry, 2020)
Herein, we report the synthesis, characterization and anticancer activity of a series of half-sandwich iridiumIII imidazole and benzimidazole N-heterocyclic carbene (NHC) anticancer complexes, and the general formula of which can be expressed as [(η5-Cpx)Ir(C^N)Cl]Cl (Cpx: pentamethylcyclopentadienyl (Cp*) or biphenyl derivatives (Cpxbiph); C^N: imidazole and benzimidazole NHC chelating ligands). Compared with cis-platin, these complexes showed interesting antitumor activity against A549 cells. Complexes could bind to bovine serum albumin (BSA) by means of static quenching mode, catalyze the oxidation of nicotinamide adenine dinucleotide (NADH) and increase the levels of reactive oxygen species (ROS). Meanwhile, these complexes could arrest the cell cycles of A549 cells and influence the mitochondrial membrane potential significantly. Due to the inherent luminescence property, laser confocal test show that complexes could enter cells followed an energy-dependent mechanism and effectively accumulate in lysosome (the value of Pearson’s co-localization coefficient is 0.70 after 1 h), further destroy lysosome integrity and induce apoptosis.